Systemic calcitonin gene-related peptide receptor antagonism decreases survival in a porcine model of polymicrobial sepsis: blinded randomised controlled trial. (May 2022) - Messerer, David A.C.; Datzmann, Thomas; Baranowsky, Anke; Peschel, Leandra; Hoffmann, Andrea; Gröger, Michael; Amling, Michael; Wepler, Martin; Nussbaum, Benedikt L.; Jiang, Shan; Knapstein, Paul; Donat, Antonia; et al.
Abstract: Background: Calcitonin gene-related peptide (CGRP) and procalcitonin, which are overexpressed in sepsis, exert distinct immunomodulatory effects mediated through the CGRP receptor. The CGRP receptor antagonist olcegepant improves survival in murine sepsis. This study evaluated whether CGRP receptor antagonism is similarly beneficial in a porcine model of polymicrobial sepsis. Methods: We conducted a prospective randomised, controlled, investigator-blinded trial in adult pigs of either sex, that were anaesthetised and ventilated before sepsis was induced by polymicrobial (autologous) faecal peritonitis. After the onset of early septic shock (systolic blood pressure <90 mm Hg or >10% decline from baseline MAP), pigs were resuscitated (i.v. fluid/antibiotics/vasopressors) and randomised to receive either i.v. olcegepant ( n =8) or vehicle control ( n =8). The primary outcome was time to death, euthanasia required up to 72 h after surgery (according to predefined severe cardiorespiratory failure), or both. Secondary outcomes included haemodynamic changes, and systemic as well as organ inflammation (mRNA expression). Results: Septic shock developed 8.7 h (inter-quartile range, 5.8–11.1 h) after the onset of faecal peritonitis. Olcegepant worsened survival, with 6/8 pigs randomised to the control group surviving 72.0 h (50.9–72.0 h), compared with 3/8 pigs receiving olcegepant surviving 51.3 h (12.5–72.0 h; P =0.01). At 48 h, lower MAP and higher cardiac output occurred in pigs receiving olcegepant. Cardiac, hepatic, and renal injury was not different between pigs randomised to receive olcegepant or vehicle. Olcegepant reduced mRNA expression of several inflammation-related cytokines and CD68 + macrophages in liver but not in lung tissue. Conclusions: CGRP receptor antagonism with olcegepant was not beneficial in this porcine model of polymicrobial sepsis, which closely mimics human sepsis.